Privacy and technology challenges for ubiquitous social networking. (24th March 2015) - Sapuppo, Antonio; Seet, Boon–Chong
Ubiquitous social networking (USN) can be seen as an evolution of ubiquitous computing supporting the social well–being of people in their everyday lives. The vision of USN focuses on enhancing social interactions among its participants during users' physical meetings. This target is leading towards important challenges such as social sensing, enabling social networking and privacy protection. In this paper we firstly investigate the methods and technologies for acquisition of the relevant context for promotion of sociability among inhabitants of USN environments. Afterwards, we review architectures and techniques for enabling social interactions between participants. Finally, we identify privacy as the major challenge for networking in USN environments. Consequently, we depict design guidelines and review privacy protection models for facilitating personal information disclosure.